Influence of the Temperature on Coccolith‐Containing Systems from Emiliania huxleyi Cultivations. Issue 5 (31st March 2020) - Chairopoulou, Makrina A.; Kratzer, Fabian; Gross, Roland; Herrmann, Michael; Teipel, Ulrich
Abstract: Thermogravimetric analysis of a coccolith‐containing biogenic broth showed a three‐step degradation process. According to this system behavior, the biogenic broth was heated to specific temperatures and characterized in terms of its morphology, surface chemistry, and crystallinity. The elemental and organic composition of the treated samples was also evaluated and compared to the reference material. The presented results were acquired in an effort to exploit pretreatment scenarios for such a biogenic system that would improve and support a separation process. Abstract : Thermogravimetric analysis data were acquired for a coccolith‐containing biogenic broth to improve subsequent separation processes of such a biogenic system. During heating, organic matter was removed from the samples. However, due to crystallinity alterations, the differences in the decomposition temperatures of the diverse compounds were considered not suitable for separation.